(3LRA ajg ef GSeg (B" (3YWGA (B"s - (3CHh GdbGSe SdjeGf Hf CMeO GjhH Hf eWjQ GddNej GdTGej GdWHQGfj,J (B360 (3g` s
(3ChdgG (B:s
(3bQCJ Ydi GdTjN GdEeGe GdMGaX TeS GdOjf CHj GdMLGL jhSa Hf Ndjd MOKfG CHh fYje CMeO Hf YHO Gddg Hf CMeO GdMGaX , MOKfG GdWHQGfi (B: (3bGd PcQ ef GSeg YWGA ef QhGI GdMOjK s
(3BNQgG (B:s
(3YWGA Hf RgjQ HUQi Qhi Yf GdCNVQ Hf YLdGf BNQg hddg GdMeO hGdefI s
(3HBNQgG SeGY Ydi GdMGaX TQa GdOjf YHO GdeDef Hf Nda GdOejGWi SfI (B702 (3hSeGYGJ ef GdCUd Gdefbhd efg HYVgG SfI (B512 (3hHYVgG (B591 (3hYdi GdfSNI NW GdMGaX GdOejGWis
(3QhGjI CHj fYje CMeO Hf YHO Gddg Hf CMeO Hf GSMGb Hf ehSi Hf egQGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B121s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN SdjeGf Hf UGdM Hf MeO Hf HSGe GdNGUI HYfjRIs
Keywords: (3GdJGQjNs